Physics in Gymnastics: Is the Perfect Iron Cross Physically Attainable?
Although many people do not realize it, physics is involved in every aspect of life. Just as in other areas, sports are inherently associated with physics in ways of which many are unaware. When one sits down to watch a football game or a gymnastics competition on television, rarely does one marvel at the extraordinary display of physics principles. However, whether or not one recognizes the role physics plays in sports, it plays a prominent one. Gymnastics is one of many sports that is performed by combining the machinery of the human body and basic physics. One particular example is the ring exercise. The body of a gymnast performing the ring exercise is subject to extreme stress, coped with by an integration of physics and biology. Although many elements of physics are incorporated into performing this procedure, I will primarily focus on one in particular- tension. By applying Newton's second law under equilibrium conditions, I will examine the question of whether or not the perfect "iron cross" maneuver on the ring exercise is phsically attainable. Do you think a gymnast can support his weight on the rings having his arms form a perfect ninety degree angle with his torso?